VD_FINDINFO HC / 2013 / 755 vom 15. November 2013 - VD Tribunal cantonal (2013)
ASSISTANCE JUDICIAIRE, AVANCE DE FRAIS, CONJOINT, HONORAIRES, AVOCAT, AVOCAT D'OFFICE, MODÉRATION | 51 al. 1 LPAv, 51 LPAv